2020
DOI: 10.1007/s00330-020-07150-8
|View full text |Cite
|
Sign up to set email alerts
|

Automated MRI perfusion-diffusion mismatch estimation may be significantly different in individual patients when using different software packages

Abstract: Objective To compare two established software applications in terms of apparent diffusion coefficient (ADC) lesion volumes, volume of critically hypoperfused brain tissue, and calculated volumes of perfusion-diffusion mismatch in brain MRI of patients with acute ischemic stroke. Methods Brain MRI examinations of 81 patients with acute stroke due to large vessel occlusion of the anterior circulation were analyzed. The volume of hypoperfused brain tissue, ADC volume, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 25 publications
4
16
0
Order By: Relevance
“…This observation was made for AIS patients with anterior circulation LVO admitted either in the early or in late time window who underwent EVT. This is in line with the study by Deutschmann et al [15] who compared RAPID® and Olea Sphere® software and reported that RAPID® outlines slightly larger ADC and smaller hypoperfused tissue volumes. They considered that small differences of the outlined regions in single slices can sum up to considerable differences in 3D volumes.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This observation was made for AIS patients with anterior circulation LVO admitted either in the early or in late time window who underwent EVT. This is in line with the study by Deutschmann et al [15] who compared RAPID® and Olea Sphere® software and reported that RAPID® outlines slightly larger ADC and smaller hypoperfused tissue volumes. They considered that small differences of the outlined regions in single slices can sum up to considerable differences in 3D volumes.…”
Section: Discussionsupporting
confidence: 92%
“…Xiong et al [14] compared two automated CT perfusion software (RAPID® and Olea Sphere®) for evaluation of AIS patients, showing that core volumes calculated with RAPID® were larger than with Olea Sphere®. The only report about MR perfusion software actually available, recently published by Deutschmann et al [15], compared RAPID® and Olea Sphere® software. They reported a small systematic difference between software, in the sense that RAPID® outlines slightly larger ADC and smaller hypoperfused tissue volumes.…”
Section: Introductionmentioning
confidence: 99%
“…The ADC lesion volume estimated by the RAPID software is likely significantly larger than that by Olea Sphere, despite the linear relationship between the volumes measured with the two softwares. 38 Thus, as the Olea Sphere evaluated ADC 620 may underestimate diffusion-positive lesion volume, the role of ADC 540 /ADC 620 ratios measured by other software, including RAPID, needs to be further investigated. Another concern is the timing (≈5–7 days after EVT) and imaging modalities used for measurement of the final infarct volume.…”
Section: Discussionmentioning
confidence: 99%
“…It is thus unknown to what extent different software applications agree regarding the same anatomical areas [ 35 ]. This issue is not only of academic interest, as volume segmentation in different software products may lead to significantly different results in the individual patient and may thus seriously influence therapeutic decisions, as was recently shown for automated MRI perfusion-diffusion mismatch volume estimation and the consecutive decision for or against mechanical thrombectomy [ 36 ]. In this study, we therefore investigated the quantitative agreement between well-established volumetric applications in a well-separated cohort and found major differences.…”
Section: Discussionmentioning
confidence: 99%